LEVEL OF FRUIT AND VEGETABLE CONSUMPTION AND NUTRITIONAL STATUS OF ADOLESCENTS SMP NEGERI 3 TABANAN - Ni Kadek Devi Ratna Sari; I Made Purnadhibrata; I.G.A Ari Widarti (Poltekkes Kemenkes Denpasar dan DPD PERSAGI Bali, 2020)
The results of the 2013 Riskesdas stated that 93.5% of the population aged more than 10 years consumed vegetables and fruits under the recommendation. This study aims to determine the level of fruit and vegetable consumption and nutritional status of adolescents. This is a cross-sectional study using 84 samples. The results of this study indicate that the majority of adolescents of Tabanan Middle School 3 have a normal nutritional status of 70.2%, thin 2.4%, fat 11.9%, and obesity 15.5%. The level of fruit consumption per day is mostly in the poor category, which is 86.9%, the category is quite 13.1%.The level of vegetable consumption per day is 57.1% for the less category and the category is 42.9%. The distribution of adolescent nutritional status based on fruit consumption levels, adolescents with underweight and normal nutritional status, fruit consumption levels were mostly in the category of 81.9%, and quite 18.1%. Adolescents who have obese and obese nutritional status have a low consumption level of 100%.Distribution of nutritional status based on the level of vegetable consumption of adolescents with underweight and normal nutritional status of vegetable consumption was 55.7% in the sufficient category, and 44.3% in the poor category. Adolescents with nutritional status fat and obese the level of vegetable consumption mostly in the less category, namely 91.3%, and 8.7% enough categories.